STRATEGI INKLUSIF DALAM PENDIDIKAN ANAK ADHD MENUJU KESETARAAN DAN KETERLIBATAN DI SEKOLAH DASAR - Dara Fitrah Dwi; Muhammad Rizky Fauzy; Dinda Lestari; Hamidah Nasution; Siti Nurhaliza; Niken Andini; Intan Mutya (STKIP Subang, 2024)
This study aims to explore inclusive strategies in the education of children with ADHD, focusing on efforts to achieve equity and inclusion in the learning environment. Children with ADHD often face challenges that affect their participation in school, so effective approaches are needed to support them. Through a literature review and analysis of best practices, this study identified various strategies, such as curriculum adaptation, teacher training, and parent involvement. The results of the study are expected to provide insights for educators and policy makers in creating an inclusive learning environment, so that children with ADHD can contribute optimally and feel accepted in the school community.